2015
DOI: 10.1016/j.jemermed.2015.07.021
|View full text |Cite
|
Sign up to set email alerts
|

First-generation Antipsychotics Are Often Prescribed in the Emergency Department but Are Often Not Administered with Adjunctive Medications

Abstract: , Abstract-Background: Although first-generation antipsychotics (FGAs) have long been used in the emergency department (ED) to treat acute agitation, little is known about how these medications are used in modern clinical practice. In particular, little work has been published about whether ED clinicians administer FGAs with adjunctive medications in accordance with expert guidelines or the prescribing practices of FGAs over time. Objectives: 1) To provide a comparison of the frequency with which FGAs are admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
3
1
Order By: Relevance
“…To our knowledge, this is the first study to create a statistical model that connects demographics and diagnoses to prescribing patterns for acute agitation in practice. Compared to previous studies11,12 assessing acute agitation treatment in the emergency department, this study showed a higher rate of combination therapy prescribing. Our study found several factors that have a significant association with the prescribing of combination therapy for acute agitation.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…To our knowledge, this is the first study to create a statistical model that connects demographics and diagnoses to prescribing patterns for acute agitation in practice. Compared to previous studies11,12 assessing acute agitation treatment in the emergency department, this study showed a higher rate of combination therapy prescribing. Our study found several factors that have a significant association with the prescribing of combination therapy for acute agitation.…”
Section: Discussioncontrasting
confidence: 76%
“…Previous retrospective studies11,12 have been completed that assess the prescribing patterns of physicians in the emergency department when treating acute agitation. However, there is insufficient data on the prescribing patterns regarding combination therapy in psychiatric units specifically, and prediction models are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past several years, expert consensus panels, most recently Project BETA, have called for improved humane practices to treat agitated patients [3]. Project BETA ("Best Evidence for the Evaluation and Treatment of Agitation") convened over 35 experts, including emergency psychiatrists, emergency medicine physicians, and mental health clinicians, preferentially recommending second-generation antipsychotics (SGAs) over the more common combination of intramuscular haloperidol + lorazepam [4][5][6][7]. SGAs were preferentially recommended orally, both to save patients the unpleasantness of needle sticks and to potentially save injury to nursing staff but the recommendation relied mostly on expert consensus instead of a comprehensive survey of available literature [8].…”
Section: Introductionmentioning
confidence: 99%
“…Emergency physicians regularly encounter agitated patients in the emergency department (ED) (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). Causes of ED-based agitation are numerous, ranging from psychosis to intoxication (2)(3)(4)(5)8).…”
Section: Introductionmentioning
confidence: 99%